A cross sectional study to find out the magnitude of “at risk” children (showing growth faltering/decline) among under-five population attending anganwadi centres in Bhopal district, Madhya Pradesh - Meena, Shailendra; Saxena, D. M.; Bankwar, Vishal; Meena, Pratibha (International Journal Of Community Medicine And Public Health, 2018)
Background: In our country the state of under-nutrition was recognized/diagnosed too late or not at all, and therefore the effort to alleviate undernutrition was also delayed. The timely recognition of “at risk” children (showing growth faltering/decline) liable for undernutrition can avert wasting; stunting and prevent severe malnutrition due to concomitant infections and other complications. Methods: A community based cross-sectional study was carried out in urban and rural area of Bhopal district, Madhya Pradesh, among under-5 children attending anganwadi centres. All the children enrolled among selected urban and rural AWCs were taken as study population. Primary information regarding “at risk” children (showing growth faltering/growth decline) was obtained by reviewing last one year growth monitoring records available. Results: There were total 10 anganwadi centres visited and growth monitoring record of last one year was analysed. There were total 1230 children enrolled in anganwadi centres under study. As per the available record we found that 416 (33.82%) of the total children enrolled in the anganwadi centres under study were “at risk” of malnutrition. The magnitude of at risk children was almost double in the urban area (43.24%) as compare to the rural area (23%). This difference was found statistically significant. Gender wise distribution of “at risk” children shows that there is marginal difference in the magnitude of “at risk” status among boys (34.57%) and girls (33.06%) and similar difference was found in urban and rural anganwadi centres under study. Conclusions: The study conclude that children belong to 2 to 4 year age group are “at risk” of under nutrition. Both the genders are equally susceptible of under nutrition though children belong to urban area had more risk as compare to rural area.